Rocking P Ranch and the second cattle frontier in Western Canada - Chattaway, Clay; Elofson, W. M. (West series (Calgary, Alta.), 2019)
"The Rocking P Ranch was one of the most ambitious family ranches in Southern Alberta. Founded in 1900 by Roderick Riddle Macleay, the Rocking P flourished during the Second Cattle Frontier as open-range the Texas System ranches failed. Beginning in 1923, Maxine and Dorothy Macleay edited, reported, and published The Rocking P Gazette, a monthly newspaper grounded in the daily life of the Rocking P Ranch. With an audience of their parents and relatives, cowpunchers, teachers, and cooks, the 12- and 14-year-old sisters set out to create a family newspaper that reflected as closely as possible the commercial publications of the time. With sections for local news, advertisements, riddles, poetry, and contributions from Macleay ranch hands, The Rocking P Gazette brings the family ranch to life. Clay Chattaway and Warren Elofson draw upon this remarkable resource to explore the Second Cattle Frontier and to tell the story of the Rocking P Ranch. Through the lens of The Rocking P Gazette, Chattaway and Elofson detail not only a system of agricultural production, but a way of life that continues to this day."--